A population study of tropical Peregrine Falcons (Falco peregrinus ernesti) in West Malaysia - Ooi, BengYean; Kéry, Marc; Percival, Robert; Lee, Zan Hui; Chiu, Sein Chiong (Zenodo, 2020)
Abstract The Peregrine Falcon ( Falco peregrinus ) is the most widely distributed bird species in the world, but very little is known about its tropical populations, where even very basic information (e.g. about population density) is mostly lacking. In January 2017, 2018 and 2019, we conducted three intensive surveys amounting to 27 days and 5,400 km driven by car in West Malaysia at latitudes between 3 and 7 °N, where the ernesti subspecies was confirmed to be a resident breeder only as recently as 1996. Here, we summarize our findings and combine them in a synthesis that includes all published and unpublished records of nesting peregrines that we could obtain in that area. In particular, we draw on the foundational work conducted by our late colleague Laurent Molard in 2003–2005. We give information about breeding habitats, local density, behavior and breeding phenology. We also describe and discuss our use of call playback during the surveys. Much more extensive reports for each survey, with plenty of photographs of all sites visited, are available upon request from the authors. According to current knowledge, Peregrines in West Malaysia nest mainly in cliffs, with some nesters on buildings exceptionally found (in Kuala Lumpur and suspected also elsewhere in cities) and possibly on large towers. Virtually all natural nesting places are limestone mountains with vertical cliffs. Owing to the mostly flat terrain in West Malaysia, with limestone cliffs only occurring very locally, the peregrine breeding distribution is extremely patchy. We found local aggregations in the regions of Ipoh (Perak), Gua Musang (Kelantan) and in the state of Perlis. However, local density is fairly low even in these hotspots, with nearest-neighbor distances in the densest cluster ranging from 3.7–5.6 km (mean 4.7). Overall, by the end of 2019, 36 occupied sites had been found in West Malaysia, of which 10 were known before 2003, 9 were found during the surveys by Mo-lard and his colleagues in 2003–2005, and 17 were new discoveries ...